Perilaku Cyberbullying pada Remaja Ditinjau Dari Empati dan Regulasi Emosi - Salsabila Aini; Wahyu Rahardjo (Jurnal Ilmu Perilaku, 2023)
The development of information technology, especially the internet, has many positive impacts, but of the many positive impacts, there are several negative impacts, one of which is cyberbullying. Teenagers are the most active social media users in Indonesia and are prone to cyberbullying behavior. There are several factors that cause adolescents to commit cyberbullying, including empathy and the ability to regulate emotions. This study aims to look at the influence of empathy and emotion regulation on adolescent cyberbullying behavior. The subjects in this study amounted to 137 adolescents with characteristics aged 18-25 years, actively using social media, having committed acts of cyberbullying in the last 6 months (such as writing comments using harsh and angry words to others, uploading photos or videos of other people's disgrace (embarrassing) without permission, ostracizing someone in online group activities, and the like). Data collection was carried out by distributing questionnaires via google form. The data analysis technique uses multiple regression. The results revealed that there was an effect of empathy and emotion regulation together on cyberbullying behavior by 7.2% with a sig. value 0,007. Separately, empathy has a negative influence of 27% with a sig. value 0.002 on cyberbullying behavior while emotional regulation has no effect on cyberbullying behavior with a sig. value 0.526. Therefore, it is important to conduct empathy training so that adolescents can increase their empathy to prevent cyberbullying.